2014
DOI: 10.1038/mt.2014.109
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Immunogenicity of Prime-boost Immunization With ChAd63 and MVA ME-TRAP From Malaria Naive to Malaria-endemic Populations

Abstract: To induce a deployable level of efficacy, a successful malaria vaccine would likely benefit from both potent cellular and humoral immunity. These requirements are met by a heterologous prime-boost immunization strategy employing a chimpanzee adenovirus vector followed by modified vaccinia Ankara (MVA), both encoding the pre-erythrocytic malaria antigen ME-thrombospondin-related adhesive protein (TRAP), with high immunogenicity and significant efficacy in UK adults. We undertook two phase 1b open-label studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 36 publications
6
63
0
Order By: Relevance
“…Reactogenicity of the ChAd63 RH5 vector was similar to that seen with the same doses of ChAd63 vectored vaccines encoding the P. falciparum antigen multiepitope string-thrombospondin-related adhesion protein (ME-TRAP), circumsporozoite protein (CSP), MSP1, or AMA1 (36-39, 52, 54) or the P. vivax antigen Duffy-binding protein region II (PvDBP_RII) (43). The same vectors encoding ME-TRAP have similarly been safe following immunization of adults, children, and infants residing in malaria-endemic areas (41,42). Our data with ChAd63 RH5 add to the growing body of evidence that this simian adenovirus vector is safe for clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactogenicity of the ChAd63 RH5 vector was similar to that seen with the same doses of ChAd63 vectored vaccines encoding the P. falciparum antigen multiepitope string-thrombospondin-related adhesion protein (ME-TRAP), circumsporozoite protein (CSP), MSP1, or AMA1 (36-39, 52, 54) or the P. vivax antigen Duffy-binding protein region II (PvDBP_RII) (43). The same vectors encoding ME-TRAP have similarly been safe following immunization of adults, children, and infants residing in malaria-endemic areas (41,42). Our data with ChAd63 RH5 add to the growing body of evidence that this simian adenovirus vector is safe for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…This heterologous prime-boost approach has shown antibody induction against difficult-to-express malaria antigens in numerous animal models, including nonhuman primates (32,34,35). These vectors, delivering antigens from P. falciparum, have now been shown to be safe and immunogenic for T cell and antibodies in healthy European and American adult volunteers (36)(37)(38)(39)(40), as well as African adults, children, and infants (41,42). More recently, similar adenovirus-poxvirus vectored vaccine technologies have been used to immunize humans against numerous other pathogens including P. vivax malaria (43), Ebola virus (44), hepatitis C virus (HCV) (45), respiratory syncytial virus (RSV) (46) and HIV-1 (47).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, the ChAd63-MVA ME-TRAP alone vaccine was tested in a Phase Ib dose escalation study in healthy Gambian and Kenyan adults (Kimani et al, 2014;Ogwang et al, 2013). The encouraging immunogenicity data of the Phase I/IIa studies in UK malaria-naïve volunteers was again confirmed.…”
Section: Liver-stage Subunit Vaccinesmentioning
confidence: 80%
“…The DNA prime/vector boost concept, has been initialy used mostly in research on vaccine against malaria (Schneider et al 2001;Kimani et al 2014). DNA priming appears to improve the outcome of boosting with recombinant proteins, or with vector-based vaccines.…”
Section: Dna Vaccination: Methods Of Deliverymentioning
confidence: 99%